Incidence and outcomes of bloodstream infections among hematopoietic cell transplant recipients from species commonly reported to be in over‐the‐counter probiotic formulations. Issue 5 (21st September 2016) - Cohen, S.A.; Woodfield, M.C.; Boyle, N.; Stednick, Z.; Boeckh, M.; Pergam, S.A.
Abstract: Background: Probiotic supplementation has been promoted for numerous health conditions; however, safety in immunosuppressed patients is unknown. We evaluated bloodstream infections (BSIs) caused by common probiotic organisms in hematopoietic cell transplant recipients. Methods: All blood culture (BC) results from a cohort of hematopoietic cell transplant recipients transplanted at Fred Hutchinson Cancer Research Center in Seattle, Washington, between 2002 and 2011 were reviewed. Patients with at least 1 positive BC for common probiotic organisms ( Lactobacillus species, Bifidobacterium species, Streptococcus thermophilus, and Saccharomyces species) within 1 year post hematopoietic cell transplantation (HCT) were considered cases. Data were collected from center databases, which contain archived laboratory data, patient demographics, and clinical summaries. Results: A total of 19/3796 (0.5%) patients developed a BSI from one of these organisms within 1 year post HCT; no Bifidobacterium species or S. thermophilus were identified. Cases had a median age of 49 years (interquartile range [IQR]: 39–53), and the majority were allogeneic hematopoietic cell transplant recipients (14/19, 74%). Most positive BCs were Lactobacillus species (18/19) and occurred at a median of 84 days (IQR: 34–127) post transplant. The incidence rate of Lactobacillus bacteremia was 1.62 cases per 100, 000 patient‐days; the highest rate occurred within 100 days post transplant (3.3 per 100, 000 patient‐days). Eight patients (44%) were diagnosed with acute graft‐versus‐host disease of the gut prior to the development of bacteremia. No mortality was attributable to any of these infections. Conclusion: Organisms frequently incorporated in available over‐the‐counter probiotics are infrequent causes of bacteremia after HCT. Studies evaluating the use of probiotics among high‐risk patients are needed.